The immune reconstitution inflammatory syndrome - Sanjay S Bosamiya (Wolters Kluwer Medknow Publications, 2011)
A paradoxical clinical worsening of a known condition or the appearance of a new condition after initiating antiretroviral therapy in HIV-infected patients is defined as immune reconstitution inflammatory syndrome (IRIS). Because of wide variation in clinical presentation and the still increasing spectrum of symptoms and etiologies reported, diagnosis remains problematic. Furthermore, no test is currently available to establish an IRIS diagnosis. Until a greater understanding of the syndrome is achieved in different regions of the world, clinicians need to remain vigilant when initiating ART and individualize therapy according to known treatment options for the specific infectious agent.